2019
DOI: 10.1038/sj.bdj.2019.45
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal diagnosis in the context of the 2017 classification system of periodontal diseases and conditions: Presentation of a middle-aged patient with localised periodontitis

Abstract: This is the second in a series of case reports demonstrating the application of the BSP implementation plan for diagnosing periodontitis patients according to the 2017 classification. Case report 2 BDJ V0.4 We discuss staging and grading of periodontitis in relation to alternative case definitions used in the epidemiologic literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…This could make treatment outcomes more predictable and improve our ability to share findings with our patients. A few examples of cases that demonstrate the practical implementation of the BPS‐I were published recently 34,35 . More importantly, the results presented in this manuscript demonstrated that the BSP's pragmatic approach through implementing a reductionist model of the original 2017 WWC neither affected the class allocation nor the prognostic performance of the system.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This could make treatment outcomes more predictable and improve our ability to share findings with our patients. A few examples of cases that demonstrate the practical implementation of the BPS‐I were published recently 34,35 . More importantly, the results presented in this manuscript demonstrated that the BSP's pragmatic approach through implementing a reductionist model of the original 2017 WWC neither affected the class allocation nor the prognostic performance of the system.…”
Section: Discussionmentioning
confidence: 78%
“…A few examples of cases that demonstrate the practical implementation of the BPS-I were published recently. 34,35 More importantly, the results presented in this manuscript demonstrated that the BSP's pragmatic approach through implementing a reductionist model of the original 2017 WWC neither affected the class allocation nor the prognostic performance of the system. This should be considered as the most significant finding in terms of practicality of implementing this classification in general dental practice.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous recent publications provide other examples detailing the application of this new classification. 8-10…”
Section: Changes To the Disease Classificationmentioning
confidence: 99%
“…In 2018, the AAP and the European Federation of Periodontology (EFP) proposed a new classification of periodontal and peri‐implant diseases and conditions 29,30 . With an explicit case definition and sub‐classifying standards for periodontitis, the renewed system is not merely instructive for daily clinical practice, 31–38 rather also suggested for epidemiological surveys.…”
Section: Introductionmentioning
confidence: 99%